(untitled) (Research, Society and Development, 2022)
Polycystic ovary syndrome (PCOS) is the most commonly diagnosed endocrine disorder in women of reproductive age. Given this,high androgen levels due to PCOS bring about bodily changes that affect sexual functioning. All these physical and psychological disorders can lead to a loss of quality of life, in addition to adversely affecting the sexual function of women with PCOS. In this context, this study aimed to investigate the pattern of sexual function in women affected by Polycystic Ovary Syndrome. The bibliographic research started from the following question "What is the pattern of sexual function in women affected by Polycystic Ovary Syndrome?", which was based on the Population, Intervention, Comparison, Outcome (PICO) model, a model used in Evidence-Based Practice (EBP). ). A total of 598 articles were found by searching the descriptors in the databases. Of this total, 145 were found on PubMed, 155 on Web Of Science, 298 on Scopus. According to the eligibility criteria, five articles were selected for this review. The review showed that women with PCOS have a higher risk of FSD than those without PCOS. Although the total FSFI scores were not significantly different across all studies, women with PCOS tended to report a lack of sexual satisfaction, decreased orgasm and arousal.